Synthesis of Schiff Bases via Condensation of Aldehydes from Ozonolysis of Purple Passion Fruit Seed Oil with Phenylhydrazine and Aniline and Their Utilization as Corrosion Inhibitor on Steel Metal (Zn) in 0.1N HCl Solution Media - Herlince Sihotang; Andreas Dani Hotman Sitio (Journal of Chemical Natural Resources, 2023)
Schiff base was synthesized through a condensation reaction between the aldehyde derived from purple passion fruit seed oil and phenylhydrazine (Schiff base I) and the aldehyde derived from purple passion fruit seed oil with aniline (Schiff base II). Aldehydes are obtained from the ozonolysis process of purple passion fruit seed oil using ozone to produce ozonides and then reduced with Zn powder in dilute acetic acid. The formation of aldehyde derivatives of purple passion fruit seed oil is supported qualitatively by the formation of a brick red precipitate through the addition of Fehling reagent and the formation of a silver mirror on the wall of the test tube with the addition of Tollens reagent and a decrease in the number of iodine compared to purple passion fruit seed oil and the results of FT-IR analysis provide a spectrum with a vibration peak at a wave number of 1744.4 cm-1 which indicates the C=O aldehyde group. The aldehyde derivative of purple passion fruit seed oil produced has an iodine value of 110.0467, which is lower than that of purple passion fruit seed oil, which is 122.0644. The formation of Schiff II base resulted in yields of 3% and 70% supported by FT-IR spectrum of vibration peaks at wave numbers 1654 cm-1 and 1602.8 cm-1, which indicated the formation of imines (-C=N-) as a result of condensation between derived aldehyde groups of purple passion fruit seed oil with amine groups of phenylhydrazine and aniline. Testing the iodine number on the Schiff I base and the Schiff II base yielded values of 124.9079 and 117.3266. A corrosion inhibitor test was carried out using the gravimetric method on HCl media with a concentration of 0.1N, 24 hours and various concentrations of compounds 1000, 3000, 5000, and 7000 ppm. Corrosion inhibitor efficiency for purple passion fruit seed oil, Schiff Base I, and Schiff Base II, respectively, were 27.87%, 88.28% and 94.08% at a concentration of 7000 ppm.